(untitled) (Modern education and development, 2024)
By analyzing how pragmatics, speech act theory, and discourse analysis are interwoven, this article emphasizes their significance in understanding human communication. Pragmatics examines how environment influences meaning, while speech act theory groups utterances based on their functions. Discourse analysis looks at language use at a level above sentences, with a focus on social interactions and structures. This article reviews pertinent literature and provides examples of practical applications to highlight the importance of these theories in a variety of fields, including linguistics, education, and technology.